Safely expanding the donor pool: brain dead donors with history of temporary cardiac arrest. (22nd January 2015) - Hoyer, Dieter P.; Paul, Andreas; Saner, Fuat; Gallinat, Anja; Mathé, Zoltan; Treckmann, Juergen W.; Schulze, Maren; Kaiser, Gernot M.; Canbay, Ali; Molmenti, Ernesto; Sotiropoulos, Georgios C.
Abstract Background & Aims Cardiac arrest (CA) in deceased organ donors can potentially be associated with ischaemic organ injury, resulting in allograft dysfunction after liver transplantation (LT). The aim of this study was to analyse the influence of cardiac arrest in liver donors. Methods We evaluated 884 consecutive adult patients undergoing LT at our Institution from September 2003 to December 2011. Uni‐ and multivariable analyses was performed to identify predictive factors of outcome and survival for organs from donors with (CA donor) and without (no CA donor) a history of cardiac arrest. Results We identified 77 (8.7%) CA donors. Median resuscitation time was 16.5 (1–150) minutes. Allografts from CA donors had prolonged CIT (p = 0.016), were obtained from younger individuals (p < 0.001), and had higher terminal preprocurement AST and ALT (p < 0.001) than those of no CA donors. 3‐month, 1‐year and 5‐year survival for recipients of CA donor grafts was 79%, 76% and 57% and 72.1%, 65.1% and 53% for no CA donor grafts (log rank p = 0.435). Peak AST after LT was significantly lower in CA donor organs than in no CA donor ones (886U/l vs 1321U/l; p = 0.031). Multivariable analysis identified CIT as a risk factor for both patient and graft survival in CA donors. Conclusion This analysis represents the largest cohort of liver donors with a history of cardiac arrest. Reasonable selection of these donors constitutes a safe approach to the expansion of the donor pool. Rapid allocation and implantation with diminution of CIT may further improve the outcomes of livers from CA donors.